Healthsaving technologies of supporting micronutrients functions of eye-sidht at students with myopia - E. Yu. Egorova; A. T. Bykov; O. A. Gromova; I. Yu. Torshin; N. N. Slushalova; N. V. Khvatova (Фармакокинетика и Фармакодинамика, 2016)
TSupport with micronutrients functions of vision in students with myopia underutilized reserve of health-saving technologies. Students myopia is one of the major problems that at the school is only growing. This paper presents the results two centers randomized trial of the effectiveness of the usage of vitamin-mineraL complex "Focus Forte" in the group of 120 young patients at the age of (1619 years, students of fuLL-time education in Ivanovo and Krasnodar) in the context of integrated therapy for 2 months. Patients were randomized to receive drug (n = 60) or controL group (standard therapy, n = 60). On day "0" day and "60" were measured more than 80 parameters of a spatiaL-contrast sensitivity with the use of speciaL computer software package. The comparison of the investigated indicators of view on the day "60" showed a number of statisticaLLy significant differences in eLectroacousticaLLy (O.S. 4,6, 95% DI 1,4-16, p = 0,03), spatiaL contrast sensitivity (O.S. 9,0, 95% DI 1,5-17, p < 0,006) and brightness sensitivity (O.S. 5,6, 95% DI 1,7-19,0; p = 0,003). The drug contributed to a statisticaLLy significant reduction of cLinicaL symptoms of hypovitaminosis, and zinc deficiency (р < 0,001). Correction of micronutrients designed to support your eyesight, promotes normaphisioLogicaL processes of vision, improve visuaL function and compensation phenomena of asthenopia among students.